Sunday

March 29, 2015

March 29, 2015

Posted by **Angela** on Sunday, July 24, 2011 at 9:12pm.

- Pre Cal -
**Reiny**, Sunday, July 24, 2011 at 10:00pm= (x+1)^2[(x+1)(4x-9) - (16x+9)]/[(x-6)(x+1)^2]

expand the square bracket and factor the result...

= (x+1)^(4x+3)(x-6)/(x-6)(x+1)^2]

= (4x+3)/(x+1) , x ≠ -1, 6

**Answer this Question**

**Related Questions**

Pre Cal - simplify the quotient: [x(5x+1)-3(x^2+1)]/ [(x-1)^2]

Pre-Calculus - Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1...

Pre-cal - let P(x)=2x^4-x^3+13^2-8x-24. Use synethetic division to show that x+1...

pre cal - (y^2)^-4y^8 simplify

Algebra - There are two solutions to | 16x - 5 | = 3. The greatest solution is ...

Pre-Cal - Simplify e^3ln2-1

PRE-CAL - SIMPLIFY 55/SQUARE ROOT OF 20 -3

Pre Cal - simplify the expression 2sin^2 t + cos^2 t-2

Pre-Cal - Classify the conic and write the equation in standard form: (1) 9x^2...

algebra - Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask ...